From outsider to insider: a look at the subculture of microdosing - Beaton, Blake (Deviant behavior, 2025)
The practice of microdosing classic psychedelic drugs (e.g. LSD [lysergic acid diethylamide] and psilocybin) has not only become more commonplace, but has also been shown to have potential in treating various psychological impairments. Much is still unknown about how people who microdose psychedelic drugs learn the processes and protocols for microdosing. To uncover how people learn the various methods and values for microdosing psychedelics, we use a subcultural lens as our framework to analyze how they transfer the various methods and values onto newcomers. Findings provide insight as to how newcomers are adopted into this community as well as how newcomers are instructed to engage in microdosing that are indicative of traditional, socially acceptable medicinal practices.